Drug Dependency as Major Problem in Academic Performance in Universities in Kenya: Maasai Mara Perspective - Iberi, Nyakundi Daniel (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2015)
The drugs and substance abuse dependency has strangled youthful population reducing them to less industrious persons at the age when they are most needed in the society. This research was carried out in response to public and government concern over increasing drugs and substance abuse dependency in the universities in the recent few years. The objective of this paper is to examine drug dependency as major problem in academic performance in universities in Kenya and describe most mitigating strategies to curb drug and substance dependency in Maasai Mara University. The descriptive survey method was found to be the most appropriate method for this study. Stratified random sampling technique was used to select a total sample of 139 respondents. Structured questionnaire were used as the main tool of data collection. The Statistical Package for Social Scientists (SPSS) Version 21 software helped to analyze the collected information in order to come up with expected analysis for interpretation and presentation. The findings of this study o established that there was high level of drugs use and substance dependency among students of Maasai Mara University. The study revealed that students who depend on drugs and substance obtain poor grades in class as compared to those who do not because they spend most of their time searching for them. Therefore, the study concludes that stringent measures should be put in place urgently so as to address the problem of drug abuse in the university. The study recommends that MaasaiMara University and other universities management to take a multifaceted strategy to minimize the vice among students.